The ACCENT-VOCBAS field campaign on biosphere-atmosphere interactions in a Mediterranean ecosystem of Castelporziano (Rome): site characteristics, climatic and meteorological conditions, and eco-physiology of vegetation - Fares, S.; Mereu, S.; Scarascia Mugnozza, G.; Vitale, M.; Manes, F.; Frattoni, M.; Ciccioli, P.; Gerosa, G.; Loreto, F. (Biogeosciences, 2009)
Biosphere-atmosphere interactions were investigated on a sandy dune Mediterranean ecosystem in a ﬁeld campaign held in 2007 within the frame of the European Projects ACCENT and VOCBAS. The campaign was carried out in the Presidential estate of Castelporziano, a periurban park close to Rome. Former campaigns (e.g. BEMA) performed in Castelporziano investigated the emission of biogenic volatile organic compounds (BVOC). These campaigns focused on pseudosteppe and evergreen oak groves whereas the contribution of the largely biodiverse dune vegetation, a prominent component of the Mediterranean ecosystem, was overlooked. While speciﬁc aspects of the campaign will be discussed in companion papers, the general climatic and physiological aspects are presented here, together with information regarding BVOC emission from the most common plant species of the dune ecosystem. During the campaign regular air movements were observed, dominated by moderate nocturnal land breeze and diurnal sea breeze. A regular daily increase of ozone concentration in the air was also observed, but daily peaks of ozone were lower than those measured in summer on the same site. The site was ideal as a natural photochemical reactor to observe reaction, transport and deposition processes occurring in the Mediterranean basin, since the sea-land breeze circulation allowed a strong mixing between biogenic and anthropogenic emissions and secondary pollutants. Measurements were run in May, when plant physiological conditions were optimal, in absence of severe drought and heat stress. Foliar rates of photosynthesis and transpiration were as high as generally recorded in unstressed Mediterranean sclerophyllous plants. Most of the plant species emitted high level of monoterpenes, despite measurements being made in a period in which emissions of volatile isoprenoids could be restrained by developmental and environmental factors, such as leaf age and relatively low air temperature. Emission of isoprene was generally low. Accounting for the high monoterpene spring emission of the dune ecosystem may be important to correct algorithms at regional and ecosystem levels, and to interpret measurements of ﬂuxes of volatile isoprenoids and secondary pollutants.
Keywords: BVOC emission; Castelporziano; Mediterranean ecosystem; stress (voyant); Water availability

Measuring, modelling and testing ozone exposure, flux and effects on vegetation in southern European conditions--what does not work? A review from Italy. - Ferretti, M.; Fagnano, M.; Amoriello, T.; Badiani, M.; Ballarin-Denti, A.; Buffoni, A.; Bussotti, F.; Castagna, A.; Cieslik, S.; Costantini, A.; De Marco, A.; Gerosa, G.; et al. (Environmental pollution (Barking, Essex : 1987), 2007)
Ozone (O3) exposure at Italian background sites exceeds UN/ECE concentration-based critical levels (CLe(c)), if expressed in terms of AOT40. Yet the occurrence of adverse effects of O3 on forests and crops is controversial. Possible reasons include (i) ability of response indicators to provide an unbiased estimate of O3 effects, (ii) setting of current CLe(c) in terms of cut-off value and accumulation level, (iii) response functions adopted to infer a critical level, (iv) environmental limitation to O3 uptake and (v) inherent characteristics of Mediterranean vegetation. In particular, the two latter points suggest that critical levels based on accumulated stomatal flux (CLe(f)) can be a better predictor of O3 risk than CLe(c). While this concept is largely acknowledged, a number of factors may limit its applicability for routine monitoring. This paper reviews levels, uptake and vegetation response to O3 in Italy over recent years to discuss value, uncertainty and feasibility of different approaches to risk assessment.
The following values have no corresponding Zotero field: accession-num: 16889878
Keywords: AOTx; Critical levels; Effects; Mediterranean Region; Ozone; Stomatal flux

Monitoring tropospheric ozone impact on plants in natural and urban areas with a Mediterranean climate - Manes, F.; Vitale, M.; Di Traglia, M. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2005)
Abstract To investigate the real linkage and effectiveness of using the AOT40 index and ozone stomatal flux (FO3) in the assessment of physiological alteration/leaf injury on clover clones sensitive to ozone and Quercus ilex plants, two statistical techniques ? Partial Least Squares (PLS) and Neural Net Analysis (NNA) ? were applied. Different results were obtained in relation to the statistical method chosen. Linear methodologies applied to clover highlighted the role of temperature (TEMP) and O3 concentration (O3Mean) in affecting photosynthesis (PHOTO), leaf injury, and stomatal conductance (COND). In Quercus plants, COND was linearly correlated to two environmental variables, TEMP and Vapour Pressure Deficit (VPD), and to two physiological variables, PHOTO and Leaf Transpiration (TRASP), whereas PHOTO was correlated with TEMP, sO3, COND and sub-stomatal CO2/external CO2 ratio (Ci/Ca). These linear relationships were, in part, modified by NNA. In fact, non-linear relationships between environmental variables, and morphological and physiological variables were evident, suggesting caution when risk assessments are made on ozone concentration-based critical levels. Both plant types showed a relationship with FO3 that negatively affected leaf injury and PHOTO in clover and Quercus plants, respectively, suggesting that ozone flux-based critical levels were more effective in linking with leaf injuries or reduction in carbon metabolism.
doi: 10.1080/11263500500333966doi: 10.1080/11263500500333966The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: AOT40; Critical levels; Neural Net Analysis; Ozone; ozone stomatal ﬂux; PLS analysis

Ozone uptake by an evergreen Mediterranean Forest () in Italy. Part I: Micrometeorological flux measurements and flux partitioning - Gerosa, G.; Vitale, M.; Finco, A.; Manes, F.; Denti, A.; Cieslik, S. (Atmospheric Environment, 2005)
Ozone, water and energy ﬂuxes have been measured over a Mediterranean evergreen forest in Central Italy from August to October 2003 with the eddy-correlation technique in order to evaluate the amount of ozone taken up by plants in dry summer and in mild autumn conditions. The stomatal ozone ﬂuxes have been calculated using the analogy with water vapor ﬂuxes inside the stomata, which are easily measurable. The total ozone dose was obtained by integrating the stomatal ﬂuxes over time. Stomatal ﬂux resulted a minor part (31.5%) of the total ozone ﬂux over the forest ecosystem. The main part of ozone deposition follows non-stomatal pathways. Chemical sink seems to play a relevant role in the morning non-stomatal deposition. Stomatal uptake is enhanced by water availability but, on the average, it does not exceed the 34.4% of the total ozone ﬂux. A comparison between the cumulated stomatal ozone ﬂuxes and the currently used AOT40 exposure index highlighted important distortions introduced by this index. AOT40, which do not take into account plant physiology, lead to substantial overestimation of ozone risk, particularly when water supply is limited, as occurs frequently in Southern European and Mediterranean areas.
Keywords: Holm oak; mediterranean forest ecosystem; ozone deposition; Stomatal uptake